1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 08:43:53
1-X+Y分之X-Y分之1+X+Y分之X-Y1-X+Y分之X-Y分之1+X+Y分之X-Y1-X+Y分之X-Y分之1+X+Y分之X-Y[(X-Y)/(1+X+Y)]/[(X-Y)/(1-X+Y)]=[(
1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
[(X-Y)/(1+X+Y)]/[(X-Y)/(1-X+Y)]
=[(X-Y)(1-X+Y)]/[(X-Y)(1+X+Y)]
=(1-X+Y)/(1+X+Y)
是要这个吗?
题目能不能明确点啊?
加个括弧什么的
(1-x+y)/(1+x+y)
化简1-x分之y分之1+x分之y
1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
2x分之1- x+y分之1(2x分之x+y -x-y)化简
x+y分之1-(x+y)的平方x-y
若X分之1+Y分之1=X+Y分之1 求X分之Y+Y分之X
x-y分之1除以y-x分之1
化简(x+y分之1)(y+x分之1)
(x-y分之1)除以(y-x分之1)
(1+x分之y)除以(1-x分之y)
y-x分之1+2y-2x分之1
1-x分之2y-x-1分之y
{(x+y)分之2-(x-y)分之1=7 {(x+y)分之1+(x-y)分之1=-1
(y分之x减x分之y)除以(y分之x-2)除以(1+x分之y)
6分之x+y+10分之x-y=3,6分之x+y-10分之x-y=-1
y分之x=2分之1,则x+y分之x-y的值为
y+x分之x-y=7分之1,求y分之x
+3分之x-y=-5,15分之x+y-2分之x-y=-1